Resilience among Children Born of War in northern Uganda - Apio, Eunice Otuko (Frontiers in Political Science, 2022)
The literature on children born of conflict-related sexual violence, or Children Born of War (CBOW) is dominated by accounts and perceptions of suffering and risks that they experience both during and after armed conflict. In contrast, this article focusses on nuanced experiences of CBOW after suffering adversities. The study applies the culturally sensitive revised 17-item Children and Youth Resilience Measure (CYRM-R) to 35 CBOW conveniently sampled from a population of those born to former forced wives of the Lord's Resistance Army (LRA) and another population born between 1993 and 2006 as a result of sexual violence perpetrated by cattle raiders in northern Uganda. Following the analysis of the CYRM-R scores, eight participants representing different quartiles, different scores on the relational/caretaker and personal resilience sub scales were identified to take part in a subsequent semi-structured interview process. The aim was to examine how CBOW in northern Uganda demonstrate resilience, the factors that influence their resilience experiences, and what it means for the broader concept of integration. Overall, CBOW are not merely stuck in their problems; past and present. Rather, findings indicate CBOW are confronting the realities of their birth statuses, and making the best use of their resources and those within the wider environment to adapt and overcome difficulties.